Securing the smart grid : next generation power grid security - Flick, Tony.; Morehouse, Justin (Amsterdam ; Boston : Syngress, 2011)
Securing the Smart Grid takes a look at grid security today, how it is developing and being deployed into now over 10 million households in the US alone. Direct attacks to smart meters as well as attacks via the networks will be detailed along with suggestions for defense against them. A framework for how security should be implemented throughout this growing system will be included directing security consultants, and system and network architects on how to keep the grid strong against attackers big and small.
Smart grid : what is it? -- Threats and impacts : consumers -- Threats and impacts : utility companies and beyond -- Federal effort to secure smart grids -- State and local security initiatives -- Public and private companies -- Attacking the utility companies -- Securing the utility companies -- Third-party services -- Mobile applications and devices -- Social networking and the smart grid -- Attacking smart meters -- Attacking smart devices -- What$1 (Bs next?s
Includes bibliographical references and index.
1
Keywords: Smart power grids -- Security measures -- United States; Electric power systems -- Security measures